PENGELOLAAN DANAU BERBASIS CO-MANAGEMENT: KASUS RAWA PENING - Partomo, Partomo; Mangkuprawira, Sjafri; Hubeis, Aida Vitayala S.; Adrianto, Luky (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2011)
Rawa Pening is an ecological system which plays an important social role for surrounding residents. Human activities which exploited it initiate crisis of fishery natural resources. Rawa Pening management could not ignore involvement of stakeholders if it is expected to be sustained. However, existing imbalance distribution of role among stakeholders, namely government and community directly depended on Rawa Pening has directed to unresolved conflicting situation and degradation of the resource. This research is intended to formulate strategic policy in managing lake based on co-management. Co-management sample determinated by purposive sampling method in four villages around Rawa Pening Lake. Analisys of the data includes stakeholders analysis, interpretative structural modelling, and co-management analysis. The research results confirm that community directly depended on the resource is the key stakeholders although they have insignificant influence on policy development and management. Co-management institution for managing the lake can be developed in order to empower community and enhance their role in managing lake’s resources. Key words: lake, stakeholders, co-management